Dependence of the collision integral on electric field - Boiko, I.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
Conductivity of charged band carriers is considered for the case when collision integral evidently depends on electric field. This dependence for the case of scattering by charged impurities results in decrease of carrier conductivity.